Clinical relevance of the expression of mRNA of MMP-7, MMP-9, TIMP-1, TIMP-2 and CEA tissue samples from colorectal liver metastases - Sutnar, Alan; Pešta, Martin; Liška, Václav; Třeška, Vladislav; Skalický, Tomáš; Kormunda, Stanislav; Topolčan, Ondřej; Černý, Radim; Holubec, Luboš (Tumor biology, 2007)
BACKGROUND: Nowadays we know that survival rates do not differ between repeated and single liver resections for colorectal liver metastases (CLM). To be able to determine patients prone to early recurrence, the use of different markers with a better prognostic value than the routinely employed tumor markers is required. AIM OF STUDY: The aim of our study was to assess mRNA expression of MMP-7, MMP-9, TIMP-1, TIMP-2 and CEA in tissue samples from CLM and their relationship to disease-free interval (DFI) and overall survival (OS). PATIENTS AND METHODS: The liver tumor biopsies were obtained from 40 patients suffering from CLM treated with radical surgery. mRNA expression levels of CEA, MMPs and TIMPs and a housekeeping gene (GAPDH) were quantified using RT-PCR. RESULTS: The increased expression of CEA, MMP-9 and TIMP-1 in CLM was associated with a short DFI and a high tendency to early CLM recurrence. Statistical analysis confirmed CEA, MMP-9 and TIMP-1 expression as prognostic factors of survival. CONCLUSION: This study demonstrated the importance of CEA, MMP-9 and TIMP-1 in the prognostication of DFI and OS. Copyright 2007 S. Karger AG, Basel.
Keywords: matrixová metaloproteinasa 7; financování organizované; dospělí; kolorektální nádory; Female; karcinoembryonální antigen; Carcinoembryonic Antigen; tkáňový inhibitor metaloproteinasy 2; Adult; ženské pohlaví; přežití bez známek nemoci; Colorectal Neoplasms; RNA nádorová; lidé; nádory jater; Survival Analysis; messenger RNA; Aged, 80 and over; Matrix Metalloproteinase 9; prognóza; RNA, Messenger; tkáňový inhibitor metaloproteinasy 1; Financing, Organized; Tissue Inhibitor of Metalloproteinase-2; Liver Neoplasms; Matrix Metalloproteinase 7; Tissue Inhibitor of Metalloproteinase-1; Adenocarcinoma; Male; matrixová metaloproteinasa 9; Aged; adenokarcinom; nádorové proteiny; Neoplasm Proteins; analýza přežití; Prognosis; Disease-Free Survival; RNA, Neoplasm; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans